RURAL TOURISM DEVELOPMENT AS A ONE VILLAGE ONE PRODUCT (OVOP) APPROACH IN WEST BANDUNG REGENCY - Iwan Koswara; Ilham Gemiharto; Dedi Rumawan Erlandia (Universitas Padjadjaran, 2020)
West Bandung Regency is a part of West Java Province, which has many rural areas that can be developed as tourism places. One that can and starts to run is through One Village One Product (OVOP). This study aims to see how rural tourism develops with the One Village One Product (OVOP) Approach in West Bandung Regency. The research approach uses a qualitative approach to explain phenomena, data collection with a library research approach, and a field consisting of in-depth interviews, observation, and Focus Group Discussion (FGD). The data analysis technique used in this study is an interactive model that classifies data analysis in three steps, namely data reduction, data presentation, and concluding. The results of this study indicate that the KBB government began the development of tourism marketing through the OVOP program approach in Kampung Pasirangsana, Tourism Village, Renda, District of Cikalongkulon. The development of Tourism Villages in KBB through the OVOP program approach is a pioneering effort that still requires a timeless process to be able to produce the expected results. Several factors hinder the development of tourism village marketing through the OVOP approach, namely limited human resources and budget. Collaboration and consistency are needed for all parties to be able to realize the goal of developing tourist villages in the West Bandung Regency.